EFEKTIVITAS LAYANAN BIMBINGAN MUHADHARAH UNTUK MENINGKATKAN KEPERCAYAAN DIRI ANGGOTA KARANG TARUNA - Rofiq Husnul Ma’afi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
This research is motivated by the problems experienced by adolescents regarding their low self-esteem. As experienced by members of the Jaga Youth Organization, Karsa Desan Joresan. Thus, the researcher aims to provideguidance services in Muhadharah order to increase the self-confidence of Karang Taruna members. This study used a quantitative experimental method with aDesign research design One Group Pretest Posttest, and for sampling the researcher used a purposive sampling technique. guidance Muhadharah services are provided to members of youth groups who are teenagers and have problems with self-confidence . Based on the data obtained by the researcher, it shows that theguidance service is MuhadharahOrganization quite effective in increasing the self-confidence of the members of the Youth. This is evidenced by the results of the paired samples t-test with the sig value. (2-tailed) of 0.000 less than 0.05, so it can be concluded that there is an effect of the service provided on' self-confidence members. Meanwhile, based on the results of thetest Ngain-,Score the average value of the control group was 72.60% with a minimum N-Gain Score of 61.70% and a maximum of 79.60%. So it can be concluded that theguidance service is muhadharah quite effective in increasing the self-confidence of the members of the Karang Taruna Jaga Jaga Karsa Joresan